Synthesis and Characterisation of Ferulate-Based Protic Ionic Liquids as a Potential Antioxidant - AHMAD, NUR AFIQAH (2019)
Ferulic acid (FA) is the most abundant natural phenolic acid in a plant cell. It is extensively used as antioxidant drug.